Staphylococcus pseudintermedius: An emerging cause of pyoderma in pet dog owner (Indian Journal of Case Reports, 2019)
Staphylococcus pseudintermedius is a part of canine skin and oral flora. It is a bacteria mainly pertaining to veterinary interest. Here, we present the case of a 40-year-old female presented in the surgical department with non-healing pyoderma for 1 year. Culture and sensitivity of the pus drained from the abscess showed S. pseudintermedius (methicillin-susceptible) identified by Vitek 2. She was treated by amoxy clavulanic and responded well with no recurrence. The patient owned a pet dog which was apparently healthy. However, her symptomatic duration started very soon after the pet dog was brought into the house. Isolation of the organism from the pet could not be done. S. pseudintermedius is an underrecognized zoonotic domestic infection. A proper clinical history and advanced diagnostic technology play a role in the identification of such infections.